Designing Cost-Effective Cash Transfer Programs to Boost Schooling among Young Women in Sub-Saharan Africa - Baird, Sarah; McIntosh, Craig; Ozler, Berk (2012)
As of 2007, 29 developing countries had some type of conditional cash transfer program in place, with many others planning or piloting one. However, the evidence base needed by a government to decide how to design a new conditional cash transfer program is severely limited in a number of critical dimensions. This paper presents one-year schooling impacts from a conditional cash transfer experiment among teenage girls and young women in Malawi, which was designed to address these shortcomings: conditionality status, size of separate transfers to the schoolgirl and the parent, and village-level saturation of treatment were all independently randomized. The authors find that the program had large impacts on school attendance: the re-enrollment rate among those who had already dropped out of school before the start of the program increased by two and a half times and the dropout rate among those in school at baseline decreased from 11 to 6 percent. These impacts were, on average, similar in the conditional and the unconditional treatment arms. Although most schooling outcomes examined here were unresponsive to variation in the size of the transfer to the parents, higher transfers given directly to the schoolgirls were associated with significantly improved school attendance and progress - but only if the transfers were conditional on school attendance. There were no spillover effects within treatment communities after the first year of program implementation. Policymakers looking to design cost-effective cash transfer programs targeted toward young women should note the relative insensitivity of these short-term program impacts with respect to conditionality and total transfer size.